2015
DOI: 10.1016/j.mechmat.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of design on the performance of steel–alumina bilayers and trilayers subject to ballistic impact

Abstract: a b s t r a c tComposite armors systems containing ceramic components are capable of offering greater ballistic protection than those of monolithic metals alone. The level of protection afforded by a composite armor depends sensitively on the materials utilized and their spatial configuration. Using numerical simulation, we investigate the effects of relevant design parameters on the ballistic performance of thin, unbonded ceramic-metal bilayers and trilayers subject to normal impact by steel spheres. The defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…However, in practice, application of confinement inevitably increases the total mass of the armour system, which may be a conflict with the optimisation to achieve best performance at the minimum weight. Results from numerical simulations [126,160] indicated that the bilayer ceramic/metal armour outperformed the trilayer metal/ceramic/metal armour in term of ballistic resistance. Note that, in the simulations, the influence of cover plate on the ballistic performance might be underestimated since the ejecting of ceramic fragments was not effectively simulated.…”
Section: Application Potential As Composite Armoursmentioning
confidence: 99%
“…However, in practice, application of confinement inevitably increases the total mass of the armour system, which may be a conflict with the optimisation to achieve best performance at the minimum weight. Results from numerical simulations [126,160] indicated that the bilayer ceramic/metal armour outperformed the trilayer metal/ceramic/metal armour in term of ballistic resistance. Note that, in the simulations, the influence of cover plate on the ballistic performance might be underestimated since the ejecting of ceramic fragments was not effectively simulated.…”
Section: Application Potential As Composite Armoursmentioning
confidence: 99%
“…The specific energy absorption capability of the armor was able to increase by setting convenient interface parameters. Holland et al 14 investigated the ballistic performance of ceramic-metal bilayered (steelalumina) and trilayered (steel-alumina-steel) structures with equivalent areal density. The ceramic-metal bilayered structure exhibited the highest ballistic resistance with the lowest back face deflection.…”
Section: Introductionmentioning
confidence: 99%
“…Analytical studies have been conducted for identifying optimized structure of these armors which have maximum Ballistic Limit Velocity (BLV) [6][7][8][9][10]. Although analytic models are useful for analysis and optimization, to achieve precise results, numerical and experimental analyses are carried out in di erent aspects, such as optimization of adhesive layer thickness [11][12][13], thickness of the ceramic tile, and back plate [14][15][16][17][18]. Also, experimental studies on compactness of the ceramic tiles [19], their size [20], and using dual-phase back plates [21] are reported in the literature.…”
Section: Introductionmentioning
confidence: 99%